Binary wavefront optimization using particle swarm algorithm. (22nd May 2018) - Fang, Longjie; Zuo, Haoyi; Yang, Zuogang; Zhang, Xicheng; Du, Jinglei; Pang, Lin
Abstract: We introduce particle swarm optimization for amplitude modulation to focus light through disordered media. Using 4096 independently controlled segments of incident wavefront, the intensity at the target is 75 times enhanced over the original intensity of the same output channel. The particle swarm optimization and existing amplitude control algorithms of focusing through scattering media are compared in the experiment. It is found that particle swarm optimization achieves the highest enhancement with less time compared with the genetic algorithm.